MOTIVASI TURKI MEMUTUSKAN HUBUNGAN DIPLOMATIK DENGAN SURIAH PADA MASA PEMERINTAHAN RECCEP TAYYIP ERDOGAN - Suri, Atika; Tjarsono, Idjang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research aims to analyze severance of diplomatic relations of Turkey toward Syria. This research aims to shows dynamics of Turkey and Syria diplomatic relations. In 2012, Turkey severance of diplomatic relations with Syria during the reign of Reccep Tayyip Erdogan cause of conflict in Syria affected greatly Turkey’s security stability, and Turkey support for the Syrian opposition and the imposes of Turkey sanctions against Syria.The perpective that applied in this research is neorealist by Kenneth Waltz, level analysis nation states. This research use theory from Donald Nuechterlien about of national interests, there are four points of basic state interests; devense of homeland, economic well-being, favorable world order, and promotion of values.This research shows that the severance of diplomatic relations carried out by Turkey againts Syria is influenced by Turkish national security interests and in the end Turkey applies sanctions againts Syria, but these sanctions do not affect the attitude of the Syrian government.Keyword: Severance of Diplomatic Relations, Syrian Conflict, Turkey National Interest.